Historia natural de Dioon merolae (Zamiaceae) en Chiapas, Mexico - Lazaro Zermeño, J.M=700 1 Gonzalez Espinoza, M.; Mendoza, A.; Martinez Ramos, M.
(Es, En)
Ilus., 101 ref.
Keywords: CYCADALES; ZAMIACEAE; FISIOLOGIA VEGETAL; CRECIMIENTO; HABITAT; HISTORIA NATURAL; DISTRIBUCION GEOGRAFICA; MEXICO